2011
DOI: 10.1108/14626001111106433
|View full text |Cite
|
Sign up to set email alerts
|

Funding of university spin‐off companies: a conceptual approach to financing challenges

Abstract: PurposeDuring the last decade, there has been an increasing focus on commercialization of knowledge and technology from universities. However, universities report financing as being the main impediment to successful university spin‐off companies (USOs) creation, leaving valuable inventions un‐commercialized. The purpose of this paper is to develop a conceptual model in order to explain financing challenges experienced by USOs.Design/methodology/approachThis paper presents a conceptual model illustrating financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Without ample access to finance, universities cannot carry out quality research that will have commercial value (Sørheim et al, 2011). Numerous studies have shown that the amount of research funding has a positive influence on university spin off activities (Lockett et .…”
Section: Determinants Of Spinoff Activitiesmentioning
confidence: 99%
“…Without ample access to finance, universities cannot carry out quality research that will have commercial value (Sørheim et al, 2011). Numerous studies have shown that the amount of research funding has a positive influence on university spin off activities (Lockett et .…”
Section: Determinants Of Spinoff Activitiesmentioning
confidence: 99%
“…Overall, when discussing the phenomenon of risk capital, researchers have relied on different combinations of concepts such as agency theory or Knightian uncertainty (e.g. Sørheim et al, 2011), asymmetric information (e.g. Wright and Robbie, 1998) and the political model theory (e.g.…”
Section: The Spectrum Of the Reviewmentioning
confidence: 99%
“…They advocate asymmetric profit distribution and compensation (Jääskeläinen et al, 2007), which leads to steady relaxing of financial constraints through reduced investment/cash flow sensitivity (Colombo et al, 2014). Finance is undoubtedly crucial for growth (Belussi and Sedita, 2015;Gompers and Lerner, 2001;Kobeissi and Wang, 2009;Mlodawska, 2012;Tyebjee and Vickery, 1988), but generally entrepreneurs tend to encounter difficulties with underdeveloped risk capital markets (Belussi and Sedita, 2015;Samitas and Kenourgios, 2005;Sørheim et al, 2011;Tyebjee and Vickery, 1988). This leads us to the next subsection, where we closely examine the entrepreneur's point of view in the extant literature.…”
Section: Focus On the Financing Partners' Perspectivementioning
confidence: 99%
“…This results in a large proportion of inventions left on the researcher's bench and unlikely ever to get to market. As detailed by Srheim, Widding, Oust, and Madsen (2011) in their work "Funding of university spin-off companies: a conceptual approach to financing challenges," investors are also reluctant to invest in early-stage companies because of the level of uncertainty compared with other investments.…”
Section: Funding Spin-offsmentioning
confidence: 99%